2007
DOI: 10.1038/ncpendmet0399
|View full text |Cite
|
Sign up to set email alerts
|

Drug Insight: clinical use of agonists and antagonists of luteinizing-hormone-releasing hormone

Abstract: This article reviews the clinical uses of agonists and antagonists of luteinizing-hormone-releasing hormone (LHRH), also known as gonadotropin-releasing hormone. In particular, the state of the art treatment of breast, ovarian and prostate cancer, reproductive disorders, uterine leiomyoma, endometriosis and benign prostatic hypertrophy is reported. Clinical applications of LHRH agonists are based on gradual downregulation of pituitary receptors for LHRH, which leads to inhibition of the secretion of gonadotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
128
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 72 publications
3
128
0
9
Order By: Relevance
“…To sustain this positive and growing trend, further and newer treatment methods must be perceived and instituted. Recent relevant advances encompass the development of three types of analogs of luteinizing hormone releasing hormone (LHRH) and the discovery of expression of receptors for the hypothalamic releasing hormones, including those for LHRH (LHRH-R), in cancer cells [6][7][8][9]. In various studies, analogs of other neurohormones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To sustain this positive and growing trend, further and newer treatment methods must be perceived and instituted. Recent relevant advances encompass the development of three types of analogs of luteinizing hormone releasing hormone (LHRH) and the discovery of expression of receptors for the hypothalamic releasing hormones, including those for LHRH (LHRH-R), in cancer cells [6][7][8][9]. In various studies, analogs of other neurohormones (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…LHRHa are 50-100 times more potent than LHRH. In addition, they have a longer duration of action due to increased receptor affinity and greater biological stability [5].Estrogens have been shown to have in vitro antioxidant effects on membrane phospholipid peroxidation [6]. The antioxidant activity of estrogens is associated with the phenol structure of estradiol and its metabolites [7].Oxidative stress (OS) substances may have a contributive role in the pathogenesis of endometriosis through the activation of macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…These are peptide analogs of hypothalamic hormones: luteinizing hormone-releasing hormone (LHRH), growth hormone-releasing hormone (GHRH), somatostatin, and analogs of other neuropeptides such as bombesin and gastrin-releasing peptide. The receptors for these peptides have been found to be widely distributed in the human body, including in many types of cancers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The regulatory functions of these hypothalamic hormones and other neuropeptides are not confined to the hypothalamo-hypophyseal system or, even more broadly, to the central nervous system (CNS).…”
mentioning
confidence: 99%
“…In particular, GHRH can induce the differentiation of ovarian granulosa cells and other cells in the reproductive system and function as a growth factor in various normal tissues, benign tumors, and malignancies (2-4, 6, 11, 14-18). Previously, we also reported that antagonistic cytototoxic derivatives of some of these neuropeptides are able to inhibit the growth of several malignant cell lines (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
See 1 more Smart Citation